Effect of educational agent and its form characteristics on problem solving ability perception of students in online task based learning media - Akyuz, Halil İbrahim; Keser, Hafize (Birlesik Dunya Yenilik Arastirma ve Yayincilik Merkezi, 2015)
The aim of this study is to investigate the effect of an educational agent, used in online task based learning media, and its form characteristics on problem solving ability perceptions of students. 2x2 factorial design is used in this study. The first study factor is the role of the educational agent and the second factor is form characteristics of the educational agent. The educational agent plays two different roles (teacher and friend). Form factor is whether the educational agent is supported by speech bubble or not. The dependent variable of this study is problem solving ability perception. The working group of the study consists of 47 students, taking ‘Multimedia Design and Creation’ classes in the spring term of 20102011 academic year in the department of Computer Education and Instructional Technologies of Ankara Universtiy. In terms of two variables, students were assigned to four different experiment groups at random. All of the experimental studies were maintained online. Measurements regarding dependent variables were carried out online. Problem Solving Inventory (PSI) is used to measure problem solving ability perceptions. Pre-test problem solving ability perception points were controlled in order to determine the effect of experimental operations on groups and post-test points were then compared. It is determined that applied method has an important effect on problem solving ability perception of students and that the educational agent in the role of teacher is more effective than the role of friend in the development of problem solving ability perception.Keywords: programming teaching, problem solving ability, educational agent.
Keywords: 4. Education; 3. Good health